2018
DOI: 10.1186/s12943-018-0922-x
|View full text |Cite
|
Sign up to set email alerts
|

TRIB2 functions as novel oncogene in colorectal cancer by blocking cellular senescence through AP4/p21 signaling

Abstract: BackgroundCellular senescence is a state of irreversible cell growth arrest and senescence cells permanently lose proliferation potential. Induction of cellular senescence might be a novel therapy for cancer cells. TRIB2 has been reported to participate in regulating proliferation and drug resistance of various cancer cells. However, the role of TRIB2 in cellular senescence of colorectal cancer (CRC) and its molecular mechanism remains unclear.MethodsThe expression of TRIB2 in colorectal cancer tissues and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 44 publications
(52 reference statements)
7
62
1
Order By: Relevance
“…Tribbles homolog 2 (TRIB2) belongs to Tribbles pseudokinases, playing a pivotal role in etiology of multifarious cancers [26,27]. Investigators found TRIB2 expression was elevated in colorectal cancer (CRC) and TRIB2 overexpression promoted cell proliferation and deferred cellular senescence of CRC partially relying on direct regulation of p21 expression and transcription factor AP4 expression [28]. In another study, promoter activity of TRIB2 might be declined in miR-206/miR-140-elevated lung adenocarcinoma cell, weakening cell invasive ability and proliferation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tribbles homolog 2 (TRIB2) belongs to Tribbles pseudokinases, playing a pivotal role in etiology of multifarious cancers [26,27]. Investigators found TRIB2 expression was elevated in colorectal cancer (CRC) and TRIB2 overexpression promoted cell proliferation and deferred cellular senescence of CRC partially relying on direct regulation of p21 expression and transcription factor AP4 expression [28]. In another study, promoter activity of TRIB2 might be declined in miR-206/miR-140-elevated lung adenocarcinoma cell, weakening cell invasive ability and proliferation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally elevated TRIB2 was previously identified as the clinically relevant factor in various subtypes of human cancers . As described previously, TRIB2 promotes tumorigenesis and induces therapeutic resistance by activating Wnt‐mediated downstream activation of Hippo signaling and the YAP pathway through transcriptional control of gene expression and TRIB2‐mediated posttranslational regulation of protein stability in liver cancer cells .…”
Section: Discussionmentioning
confidence: 66%
“…Abnormally elevated TRIB2 was previously identified as the clinically relevant factor in various subtypes of human cancers. [5][6][7][8] As MAP3K1 is a 196-kDa serine/threonine kinase that is activated by various stimuli and cell stresses, including growth factors, cytokines, and microtubule disruption. 35 Our present study showed elevated MAP3K1 expression in glioma, which is conversely associated with a poor prognosis and therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although miR-509-5p should have many targets, for example, MDM2, SOD2, FOXP1, etc., we identified TRIB2 as a direct target of miR-509-5p while it is a putative oncogene that is also highly expressed in OS tissues. Furthermore, the result of subsequent luciferase reporter gene suggested that TRIB2 inhibited the bioactivity of a well-recognized tumor suppressor gene, p21, through blocking its transcriptional activity [17]. In conclusion, miR-509-5p acts as an antitumor gene in OS through inhibiting the expression of TRIB2, an oncogene that decreased the expression of p21 and attenuated the antitumor function, thus increasing cancer risk and accelerating the OS progression.…”
Section: Discussionmentioning
confidence: 89%